Building Trust: Communication and Subordinate Trust in Public Organizations - Greg PORUMBESCU; Jungho PARK; Peter OOMSELS (Transylvanian Review of Administrative Sciences, 2013)
This research explores how communication strategies of supervisors in public organizations influence subordinates’ trust in their supervisors and organization. At present, little public administration research has explored how the pattern of communication influences subordinates’ trust in their supervisors or organization (vertical trust), in detail. As such, this research constructs a conceptual framework of how supervisors’ communication with subordinates can affect vertical trust in public organizations. Using 2010 US Federal Employee Viewpoint Survey Data, this research uses structural equation modeling to empirically assess the aforementioned framework. The broad conclusion drawn is that interpersonal communication strategies are most effective in building vertical trust in public organizations.